oltammetric studies on microcrystalline C60 adhered to an electrode surface by solvent casting and mechanical transfer methods - Tan, W.; Lim, E.; Bond, A. (Springer, 2003)
Voltammetric studies on C60 fullerene particles adhered to an electrode surface by solvent casting or mechanical transfer exhibit evidence of nucleation and growth controlled processes for the C600/- and C60-/2- solid state when the modified electrode is in contact with acetonitrile solutions containing NBu4+ electrolyte. Although peak potentials and peak separations are dependent on scan rate as well as the amount of deposit and temperature, potentials obtained using a zero-current extrapolation method are almost independent of all these parameters. These data enable reversible potentials of -816 and -1168 mV vs. Ag/Ag+ to be obtained in acetonitrile (0.1 M NBu4PF6) respectively for the processes: C60(solid) + NBu4+(solution) + e- ⇌ NBu4 C60(solid) and NBu4C60(solid) + NBu4+(solution)+ e- ⇌ (NBu4)2C60(solid). Images obtained by scanning electron microscopy reveal that both the crystalline and particle size is enhanced by 60 s of reductive electrolysis, with the detected (NBu4)2C60 crystals being slightly larger than those of (NBu4)C60. After a short period of potential cycling or controlled potential electrolysis, it is concluded that the data obtained by either method of surface adherence are almost indistinguishable, as are their morphologies.